Strategi Efektif Dalam Mengembangkan Kecerdasan Emosional Siswa Melalui Bimbingan Konseling - Nursakinah, Nursakinah (CV. SINAR HOWUHOWU, 2024)
Mental well-being is an important factor in supporting the academic and social success of students. Counseling plays a strategic role in improving mental well-being by providing the emotional and psychological support needed in the educational environment. This article discusses the role of counseling as a preventive and curative effort in addressing mental health issues among students. By focusing on the role of counselors, the interventions carried out, and the challenges faced in implementing counseling services, this study concludes that effective counseling services can enhance students' mental well-being and minimize potential psychological problems. However, there are still various barriers that need to be addressed in order to optimize the role of counseling in education.